Cormorants as a Potentially Important Reservoir and Carrier of Newcastle Disease Virus on the Asian Continent - Karamendin, Kobey; Kydyrmanov, Aidyn (Frontiers in Veterinary Science, 2021)
Despite numerous disease prevention measures and control programs, Newcastle disease (ND) remains one of the most significant infections in poultry worldwide, especially in developing countries. It is known that wild birds, mainly of the Anseriformes order, are the main carrier of lentogenic (non-pathogenic) variants of Newcastle disease virus (NDV) in nature. But the question of the reservoir of velogenic (highly pathogenic) NDV in nature still remains open. In the 1970s, 1990s and 2000s in North America during epizootics among cormorants, velogenic NDV strains were isolated. It was later concluded that cormorants play an important role in the maintenance and circulation of NDV in North America. New data have been obtained on the circulation of velogenic NDV strains in wild birds in Central Asia: VIIb and XIII genotype strains were isolated from cormorants for the first time in Kazakhstan. Interestingly, outbreaks of NDV registered in poultry in Central and Southern Asia were phylogenetically close to the viruses from cormorants that support the idea that cormorants can serve as the potential reservoir of velogenic NDV in developing countries of Asia. The seasonal migrations of cormorants may contribute to the distribution of the virus throughout Asia but more evidence must be obtained to confirm this hypothesis. There is increasing evidence of the introduction of NDV into poultry farms from wild nature worldwide. This article continues the discussion on the likelihood of cormorants to serve as a reservoir and carrier of NDV on the Asian continent.